Association Between Non-Alcoholic Fatty Liver Disease, Metabolic Dysfunction-Associated Fatty Liver Disease and the Risk of Chronic Kidney Disease in patients aged ?18 years: A Systematic Review - Putu Ngurah Pradnya Wibawa; Ni Putu Lia Juliantini; Ni Luh Putu Serly Ekayanti (Publikasi Indonesia, 2026)
Non-alcoholic fatty liver disease (NAFLD) is a chronic liver condition whose prevalence continues to rise in parallel with increasing rates of obesity, insulin resistance, and other metabolic disorders. NAFLD is also associated with extrahepatic conditions, including chronic kidney disease (CKD). This study aimed to determine whether there is an association between NAFLD and the incidence of CKD. This scoping review analyzed articles published between August 2016 and August 2026 from PubMed, ScienceDirect, and OpenAlex. The inclusion criteria comprised English-language cohort studies, case-control studies, and cross-sectional studies examining the association between NAFLD and the risk of CKD. Fifteen articles were selected following a rigorous screening process. The findings indicate a consistent and significant association between fatty liver disease—particularly metabolic dysfunction-associated fatty liver disease (MAFLD) and metabolic dysfunction-associated steatotic liver disease (MASLD)—and an increased risk of incident CKD. MAFLD appears to be a better predictor of chronic kidney disease (CKD) than the traditional NAFLD definition, primarily because it directly incorporates metabolic dysfunction. The terminology has evolved from non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated fatty liver disease (MAFLD). This shift represents a change in diagnostic strategy from exclusion-based criteria (as in NAFLD) to inclusion-based criteria that prioritize metabolic dysfunction (including obesity and diabetes), which has been shown to be more effective in assessing the risk of developing CKD.